2008
DOI: 10.1016/j.virol.2008.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Requirements of the membrane proximal tyrosine and dileucine-based sorting signals for efficient transport of the subtype C Vpu protein to the plasma membrane and in virus release

Abstract: Previously, we showed that the Vpu protein from HIV-1 subtype C is more efficiently transported to the cell surface than the well studied subtype B Vpu (Pacyniak et al., 2005) and that a SHIV expressing the subtype C Vpu exhibited a decreased rate of CD4+ T cell loss following inoculation in macaques (Hill et al., 2008). In this study, we examined the role of overlapping tyrosine-based (YXXPhi) and dileucine-based ([D/E]XXXL[L/I]) motifs in the membrane proximal region of the subtype C Vpu (EYRKLL) in Vpu intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 59 publications
(61 reference statements)
3
27
2
Order By: Relevance
“…These findings raise the possibility that subtype B Vpu TGN-to-endosome trafficking may not be actively regulated and may indeed occur by bulk flow. These results are in sharp contrast with recent observations made by Ruiz et al, which found that the mutation of the conserved Tyr residue in the hinge region of subtype C Vpu drastically decreased the viral replication of simian-HIV virus encoding subtype C Vpu (27). This same group also showed that the mutation of the second leucine (L39G) of the dileucine-based motif (EYRKLL) of subtype C Vpu leads to a protein that is transported to the cell surface less efficiently, with the majority retained within the Golgi complex (27).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings raise the possibility that subtype B Vpu TGN-to-endosome trafficking may not be actively regulated and may indeed occur by bulk flow. These results are in sharp contrast with recent observations made by Ruiz et al, which found that the mutation of the conserved Tyr residue in the hinge region of subtype C Vpu drastically decreased the viral replication of simian-HIV virus encoding subtype C Vpu (27). This same group also showed that the mutation of the second leucine (L39G) of the dileucine-based motif (EYRKLL) of subtype C Vpu leads to a protein that is transported to the cell surface less efficiently, with the majority retained within the Golgi complex (27).…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in sharp contrast with recent observations made by Ruiz et al, which found that the mutation of the conserved Tyr residue in the hinge region of subtype C Vpu drastically decreased the viral replication of simian-HIV virus encoding subtype C Vpu (27). This same group also showed that the mutation of the second leucine (L39G) of the dileucine-based motif (EYRKLL) of subtype C Vpu leads to a protein that is transported to the cell surface less efficiently, with the majority retained within the Golgi complex (27). It is therefore likely that the distinct requirement of subtype C and subtype B Vpu for tyrosine-and dileucine-based sorting signals is related to the activity of their respective sorting motifs as well as their different patterns of localization.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Columns on the far right indicate the presence (ϩ) or absence (blank) of previously described transport and/or degradation motifs in the intracellular domain of Vpu. These include a Yxx⌽ motif scored as Yxx(L/M/V/I/F/W) (8,21,56), a ␤-TrCP ubiquitin-dependent degradation signal scored as D(S/D/E)Gxx(S/D/E) (28,39), and a putative trafficking signal scored as (D/E)xxxL(L/V/I/M) (33).…”
Section: Discussionmentioning
confidence: 99%